Anxiety (Advancements in Homeopathic Research, 2022)
A new concept is added by Research scientist in Homoeopathy that modalities especially of aggravation concerning can be included as anxiety in mind section for selection of remedy, e.g. a patient is getting eye pain while watching T.V. mean eyeache < T.V. watching, so in mind section of repertory under anxiety, we take a look as rubric exertion of eye and can get remedy from there which gives prompt relief. Dr. Paschera Tomas Pabello from Argentina who was first practitioner in Homoeopathy practiced successfully throughout his life taking mind symptoms specially and cured many cases. This anxiety concept concerning the modalities as a new rubric can be so helpful in practice for any homoepath.Our Indian homoepath Late Dr. H.L. Chitkara (Ex – editor Homoeopathic Heritage International) and Dr. M.L. Sehgal (Revolutionized School of Homoeopathy) also used the technique to treat patient based upon mind symptoms alone by considering present, persisting & predominating Mind symptoms.
Keywords: Anxiety; Homoeopathy; modalities especially; predominating Mind symptoms